A cross-sectional study on the severity of gingivitis among Filipino pregnant women - Alano, Ma. Christina M.; Frange, Melanie Ruth Karganilla (Adviser).
Foreign studies have been conducted concerning the period during which pregnancy gingivitis peaks, the results being variable. At present, no local studies have been documented regarding the severity of gingivitis among a group of Filipino pregnant women. It was then the main objective of the study to identify the trimester(s) at which gingivitis is most severe among Filipino pregnant women. The study undertaken was a cross-sectional study which examined 49 pregnant women who were in different trimesters of pregnancy and who visited the Out-Patient Department of the Philippine General Hospital, Obstetrics Department. An oral examination was conducted employing the PBI scoring system. The number of subjects examined for the first trimester were inadequate in order to derive any conclusions from the data. Between the second and third trimesters, the most number of severe cases of gingivitis occurred in the third trimester. Moderate gingivitis was the predominant degree of inflammation during the second and third trimesters. There was no significant difference between the degree of inflammation of the second and third trimesters.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.